PDF Enhancing Sharia Management as a Development Stage in the Business Sector: Peningkatan Manajemen Syariah Sebagai Tahapan Perkembangan Di Sektor Bisnis - Nur Fadilah; Ulya Ardhia Cahyani Ahmad (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2025)
The implementation of Sharia management is becoming increasingly important in the face of global industrial competition, where ethics, sustainability, and brand trust are key determinants of competitiveness. While previous studies have largely focused on the impact of Sharia management in the financial sector, research integrating Sharia principles into cross-sector industrial development strategies remains limited. This study aims to construct a conceptual framework explaining the strategic role of Sharia management in enhancing industrial competitiveness and sustainability.This research employed a systematic literature review with a qualitative descriptive approach, covering publications from 2015 to 2024 obtained from reputable databases (Scopus, Web of Science, ProQuest, Google Scholar, DOAJ). Data were analyzed using content analysis to identify themes, map influence mechanisms, and draw strategic implications. The findings reveal three primary pathways through which Sharia management influences industrial development: (1) ethics–reputation–competitive advantage, (2) risk management–financial stability–growth, and (3) sustainability–social license–global market access. The integration of these pathways strengthens the industrial position in both the global halal market and the broader ethical market. This study has implications for the development of Islamic value-based management theory, the formulation of national industrial policies, and sustainable business strategies aligned with maqasid al-shariah principles and international ESG standards.